2019
DOI: 10.31018/jans.v11i3.2085
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and status of migratory and resident wetland birds in Haridwar, Uttarakhand, India

Abstract: Migration is the seasonal habitual movement, exhibited by many avian species along a flyway from breeding to wintering grounds and vice versa all over the world. Migratory birds are very sensitive to even small changes in water level which may be affected by flood or drought on their breeding and wintering grounds. High rains during monsoon season can cause flood conditions in the lower hills and Gangetic plains including Haridwar district. In our study, conducted during last ten years (2009-2018), we covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Some previous studies (Tanveer et al, 2019, Ahmed et al, 2019, Ghosh, et al, 2018, Bhattacharjee and Bargali, 2013) also indicated that aquatic habitats are best for residential as well as visiting avifauna species. The aquatic habitat adjoined with forest, shrub, and agricultural patches attracts more numbers of avian species due to good sources of food and nesting shelters (Singh et al, 2019). During this study period, we were able to make observations in different habitats (Figure 2-4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies (Tanveer et al, 2019, Ahmed et al, 2019, Ghosh, et al, 2018, Bhattacharjee and Bargali, 2013) also indicated that aquatic habitats are best for residential as well as visiting avifauna species. The aquatic habitat adjoined with forest, shrub, and agricultural patches attracts more numbers of avian species due to good sources of food and nesting shelters (Singh et al, 2019). During this study period, we were able to make observations in different habitats (Figure 2-4).…”
Section: Resultsmentioning
confidence: 99%
“…The study area is listed as an important bird area (Islam and Rahmani, 2004). Many avian species migrate from a short to a very long distance every year while other species are non-migratory and spend their life cycle in a particular area (Arya et al, 2019). Our study area hosts many types of resident and migratory species.…”
Section: Introductionmentioning
confidence: 99%
“…They remove animal waste like carcasses of livestock and wild animals and carrion from the environment (Singh and Bisht, 2019). Water streams provided a suitable habitat for many waterbird species such as kingfishers and duck species (Arya et al, 2019). The study covers some agricultural land and agricultural land to support avian diversity due to some alternative food resources such as seeds and invertebrates (Figueroa & Corales, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The last decade has been devoted to avian variety and conservation. (Naithani and Bhatt, 2010, Bhatt and Joshi, 2011, Joshi and Bhatt, 2015, Saini et al, 2017, Arya et al, 2019 where studies have been conducted on avifaunal diversity in forest habitat, wetlands, mangroves, and agriculture habitat in India (Singh, 2002). The Himalayan foothills are globally identified as a good biological diversity, supported by the complex and consequent climatic and edaphic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been mentioned that wetland provides a unique habitat for many residential bird and migratory bird species (Zhijun, et al, 2010;Ghasemi, et al, 2012;Shao et al, 2014;Bhatt, 2015;Saini et al, 2017;Arya et al, 2019;Wanna et al, 2020. Some studies in India (Kaushik et al, 2013, Bhatt et al, 2015, Saini et al, 2017, Arya et al, 2019 have been reported wetland provides good shelter, food, and enhance the waterbird diversity.…”
Section: Introductionmentioning
confidence: 99%